ANALYSIS OF DISCRIMINATORY GAME VARIABLES BETWEEN WINNERS AND LOSERS IN WOMEN'S HANDBALL WORLD CHAMPIONSHIPS FROM 2007 TO 2017: Discriminatory variables in women’s handball championships (Kinesiology, 2020)
The aim of this study was to identify game variables that discriminate winning from losing teams and to understand how these variables contribute to victory by observing differences of goals in matches of women's handball world championships. The sample comprised 471 games between 2007 to 2017. The games were grouped into three clusters (balanced games - difference of 1 to 8 goals; unbalanced games - difference of 9 to 20 goals; very unbalanced games - difference of > 20 goals). In comparisons of means, the performance of winning teams is significantly higher (most variables), or lower in the case of number of technical fouls (p < .05). In balanced games, there is a greater contribuition of defensive variables (stollen balls, blocked throws and goalkeeper efficiency) in relation to attack variables (attack efficiency and throw efficiency). For victory, the number of technical fouls reduces to a lesser extent the chances of winning. Games with unbalanced and very unbalanced scores seem to follow a same tendency. We conclude that the decisive variables for victory showed a greater weight with a special emphasis on stolen balls followed by offensive variables (throw efficiency, attack efficiency and technical fouls) in balanced games.